Case Report: Kehamilan Ektopik Terganggu pada G3P1A1 Wanita 29 Tahun - Hasta Hendarto; Rasmi Zakiah Oktarlina; Intan Kusumaningtyas (Medula, 2026)
Ectopic pregnancy is a condition in which the gestational sac is located outside the uterine cavity, representing the most common life-threatening emergency during the first trimester of pregnancy. Implantation in ectopic pregnancy frequently occurs in the fallopian tube. The clinical manifestations are typically characterized by amenorrhea, followed by vaginal bleeding and sudden onset abdominal pain. In this case, a 29-year-old woman, G3P1A1, presented at 6–7 weeks of gestation with severe lower abdominal pain accompanied by vaginal bleeding, along with a risk factor of a previous history of ectopic pregnancy. Data were obtained through anamnesis, general physical examination, obstetric assessment, ultrasonography, and both medical and non-medical management. Physical examination revealed conjunctival pallor, abdominal distension with muscular defense, tenderness in the lower abdomen, and a non-palpable uterine fundus. Pelvic examination demonstrated cervical motion tenderness and bulging in the pouch of Douglas. Ultrasonography findings were highly suggestive of ectopic pregnancy. The diagnosis was established as gravida 3 para 1 abortus 1, 6–7 weeks of gestation, with a complicated ectopic pregnancy. The patient underwent exploratory laparotomy with left salpingectomy due to rupture of the left ampullary segment of the fallopian tube. Methotrexate therapy was not administered, as the patient did not meet the eligibility criteria for medical management, given that tubal rupture had already occurred.